Numerical Analysis On Static And Dynamic Behavior Of Additively Manufactured BCC Lattice Structures - Ismail, Rainah; Putra, Azma; Azmi, Muhamad Syafwan; Nurdin, Muhammad Nasruddin (Bangladesh University of Engineering and Technology, 2021)
This research aims to investigate the effect of the strut diameter of lattice structures on their vibration characteristic numerically. The finite element analysis (FEA) method was validated beforehand in experimental work with lattice structure fabricated using fused deposition modeling (FDM) additive manufacturing (AM). From the comparison, good agreement was achieved with less than 11% error. From numerical results, it was found the stiffness values decrease with strut diameter from 1.8 mm to 1.0 mm. The first three vibration modes show steady increment around 12 Hz, 20 Hz, and 70 Hz in natural frequency respectively for acrylonitrile butadiene styrene (ABS) material and roughly 35 Hz, 60 Hz, and 200 Hz for both stainless steel and titanium as the strut diameter increase by 0.2 mm each. The validated FEA models can be used for exploration on many other materials and design parameters without having to conduct experimental work which helps for sustainability.